The gut–brain axis: historical reflections. Issue 2 (23rd November 2018) - Miller, Ian
ABSTRACT: The gut–brain axis and the microbiome have recently acquired an important position in explaining a wide range of human behaviours and emotions. Researchers have typically presented developments in understandings of the microbiome as radical and new, offering huge potential for better understandings of our bodies and what it means to be human. Without refuting the value of this research, this article insists that, traditionally, doctors and patients acknowledged the complex interactions between their guts and emotions, although using alternative models often based on nerves or psychology. For example, nineteenth-century doctors and patients would have been well acquainted with the idea that their stomachs and minds were somehow connected, and that this interaction could produce positive or negative physical and mental health impacts. To demonstrate this, this article offers a snapshot of medical and public thought on (what we currently call) the gut–brain axis in the nineteenth and twentieth centuries, using Britain as a key case study due to the prevalence of gastric problems in that country. It commences by exploring how nineteenth-century doctors and patients took for granted the intimate relations between gut and mind and used their ideas on this to debate personal health, medical theory and social and political discourse. The article then moves on to argue that various medical sub-disciplines emerged (anatomy, physiology, surgery) that threatened to reduce the stomach to a physiologically complex organ but, in doing so, inadvertently began to erase ideas of a gut–mind connection. However, these new models proved unsatisfactory, allowing more holistic ideas of the body–mind relationship to continue to carry currency in twentieth-century psychological and medical thought. In the late century, pharmacological developments once again threatened to minimise the gut–brain axis, before it once again became popular in the early twenty-first century, now debated through a new language of microbiology.